On doubly stochastic operators defined on infinite dimensional space - Mukhamedov, Farrukh; Shahidi, Farruh (UPM Press, 2009)
We give a defination of doubly stoshastic quadratic operator, defined on infinite demensional space and prove necessary condition for doubly stochasticity of such operators.